The evolution of electronic media of the Republic of Kazakhstan (Herald of Journalism, 2019)
For more than twenty-five year history of independence of the Republic of Kazakhstan on the media market has undergone significant changes in the development of information policy. The format and quality of television programs has changed, and the essence of these changes is complex and diverse. In many ways, precisely because of these changes, television is not only retains its significance, but also becomes a universal channel for exposure to the material and spiritual historical experience through which society preserves, converts or multiplies the knowledge and world outlooks.It can be argued that in the age of information technology TV is still an effective instrument of value orientation of the individual and stands today not only as a means of mass media and communication, but also as a mirror, the projection of the entire objective reality. This, in our opinion, due to the fact that the structure of society all the time in the mobile state. It is changing, becoming other, experiencing a different kind of influence related to a number of reasons of socio– political, technological, aesthetic, cultural, psychological order. In all this diversity, the social significance of television is increasing, but at the same time, the responsibility that it should have in relation to a changing audience is increasing. If various types of causes affect its change, then these same factors also affect the target attitudes and characteristics of the modern media audience.The problem of duality arises, which acquires the specific features of globalization. Television affects the mass audience, while the modern mass audience, demands from television to meet its changing tastes. It also highlights the relevance of articles devoted to the issues of transformation and evolution of television programs, which must remain in demand. As among traditional media, television is the most popular type.In addition, it is necessary to take into account the fact that, using specific methods of influencing the audience, the media have always influenced the mass consciousness. And for the media, this is the most important part of the public consciousness, which performing a mobilization function can “move” society in a given direction. Therefore, the article raises and opens the question of what are the attitudes and values can carry the evolution of modern television to society, whether it is consistent with the social and technological installations that should exist and develop a democratic society in its translational motion.
Keywords: television of the Republic of Kazakhstan, evolution of genres, electronic media, mass audience, information field, television broadcasting, independent media.